Implementasi Baik dan Buruk dalam Filsafat Akhlak Menurut Perspektif Muhammad Taqi Mishbah Yazdi - Arif, Basyir; Arif Dwi Haryanto (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
This study discusses the theory of good and bad in the moral conception of Muhammad Taqi Mishbah Yazdi, one of the contemporary Iranian philosophers. an Iranian Shia cleric as well as a conservative political activist who serves as the spiritual leader of the Islamic Revolutionary Stability Front in Iran. He was born in the city of Yazd, Iran, on Rabi'ul Awal 1353 Hijri (1934). It was also in the city of Yazd that Muhammad Taqi Mishbah Yazdi began and completed the basic studies of Islamic sciences by reading classical texts. Where Muhammad Taqi Mishbah Yazdi stands on his rational argument, he considers that humans are able to know what good and bad mean independently. And the moral arguments of Muhammad Taqi Mishbah Yazdi are built on epistemological conditions. In his formulation, he also makes references to western thought (pragmatism and utilitarianism). And what influenced him the most was the idea of transcendentalism in the philosophy of Mull Shdr. But Muhammad Taqi Mishbah Yazdi only capitalized on these ideas and gave his own original thoughts.